1997
DOI: 10.1139/b97-097
|View full text |Cite
|
Sign up to set email alerts
|

The impact of eucalypt on the leaf-associated aquatic hyphomycetes in Spanish streams

Abstract: Aquatic hyphomycete assemblages on decomposing leaf litter of the exotic species Eucalyptus globulus Labill. were compared with those on the native riparian species Alnus glutinosa (L.) Gaertn. in three low-order streams of the Agüera watershed (Basque Country – Cantabria, Spain). These streams contrast by the importance of eucalypt in the riparian vegetation and by the nutrient contents in the water. Neither the total conidial production nor the number of fungal species differed between the two leaf species i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
43
2
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 13 publications
9
43
2
2
Order By: Relevance
“…Moreover, the establishment of exotic riparian plants can alter the exchange of organic material between terrestrial and lotic ecosystems, both changing the quantity (Mineau et al 2011(Mineau et al , 2012 or the quality (B€ arlocher & Graça 2002) of terrestrial litter inputs, leading to alterations in the composition (Serra et al 2013) and density (Lester et al 1994) of benthic assemblages. Many studies have shown that, for instance, the introduction and spread of Eucalyptus globulus plantations in Spain had a strong effect on in-stream terrestrial detritus colonization and degradation (Chauvet et al 1997;Pozo et al 1998;Ferreira et al 2006), while other studies have shown weak influence of exotic species on streams (Braatne et al 2007). Our study gave evidence that mass loss of leaf bags was generally higher in the unpolluted site A rather than in the polluted site B.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the establishment of exotic riparian plants can alter the exchange of organic material between terrestrial and lotic ecosystems, both changing the quantity (Mineau et al 2011(Mineau et al , 2012 or the quality (B€ arlocher & Graça 2002) of terrestrial litter inputs, leading to alterations in the composition (Serra et al 2013) and density (Lester et al 1994) of benthic assemblages. Many studies have shown that, for instance, the introduction and spread of Eucalyptus globulus plantations in Spain had a strong effect on in-stream terrestrial detritus colonization and degradation (Chauvet et al 1997;Pozo et al 1998;Ferreira et al 2006), while other studies have shown weak influence of exotic species on streams (Braatne et al 2007). Our study gave evidence that mass loss of leaf bags was generally higher in the unpolluted site A rather than in the polluted site B.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies examining particular components of the community (individual taxa) or relative abundance distributions such as evenness or dominance degrees [11,50]. The natural variability of these communities is often overlooked, and most studies only compare a given reference situation with others supposedly impaired.…”
Section: Introductionmentioning
confidence: 99%
“…Eucalyptus leaves attained the maximum ergosterol content reached by alder on day 28, on day 56. BÄRLOCHER et al (1995), andCHAUVET et al (1997) also noticed a delay between fungal colonisation of alder and eucalypt leaves. The latter reached a higher value than alder (day 171, approximately 400 µg ergosterol/g dry mass), probably because it can support higher fungal biomass (eucalypt leaves are thicker than alder leaves).…”
Section: Discussionmentioning
confidence: 88%
“…Succession studies during litter decay in aquatic systems have been confined to single biological groups such as macroinvertebrates (e.g., BASAGUREN and POZO, 1994;ROBINSON et al, 1998;COLLIER and HALLIDAY, 2000), and aquatic hyphomycetes (e.g., CHAUVET et al, 1997). These asexual and filamentous fungi are often found on decomposing leaves, wood and twigs in wellaerated water bodies.…”
Section: Introductionmentioning
confidence: 99%